The clinical characteristics of patients with IgG4-related disease with infiltration of the labial salivary gland by IgG4-positive cells. Issue 6 (November 2014) - Abe, Ayumi; Takano, Kenichi; Seki, Nobuhiko; Jitsukawa, Sumito; Yamamoto, Motohisa; Takahashi, Hiroki; Himi, Tetsuo
Abstract Objectives. Mikulicz's disease (MD) is an immunoglobulin (Ig) G4-related disease with systemic symptoms. Submandibular gland (SMG) biopsy is recommended for patients with possible IgG4-related MD for accurate differential diagnosis; however, it is difficult for certain patients to undergo this procedure. In contrast, labial salivary gland (LSG) biopsy is more convenient. Here we present an analysis of patients with IgG4-related MD whose LSG specimens were infiltrated with abundant IgG4-positive plasma cells. Methods. Sixteen patients diagnosed with IgG4-related MD underwent simultaneous SMG and LSG biopsies. We evaluated patients' serological and 18F-fluoro-2-deoxyglucose-positron emission tomography/computed tomography (18F-FDG-PET/CT) and grouped them as LSG+ (LSG specimens with > 40% IgG4-positive plasma cells/IgG-positive plasma cells, 11 patients) or LSG− (LSG specimens with < 40% IgG4-positive plasma cells/IgG-positive plasma cells, 6 patients). Results. There were not significant differences in serum IgG and IgG4 levels between the two groups; however, serum concentrations of soluble interleuikin-2 receptor (sIL-2R) were significantly higher in the LSG+ group. All patients with increased 18F-FDG uptake in their parotid glands were a part of the LSG+ group. Conclusions. When a SMG biopsy is not possible, the serum concentration of sIL-2R and 18F-FDG-PET/CT findings may predict whether LSG biopsy will facilitate the diagnosis of IgG4-related MD.